2011
DOI: 10.1111/j.1939-165x.2011.00335.x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinicopathologic abnormalities associated with snake envenomation in domestic animals

Abstract: Envenomation of domestic animals by snakes occurs frequently in certain geographic areas.However, reports describing clinical signs, clinicopathologic abnormalities, therapeutic approaches, and outcomes are sparse. This review summarizes various snake families, venom types associated with harmful snakes, and the significant hematologic, hemostatic, and biochemical abnormalities associated with envenomation. Hematologic abnormalities include RBC membrane abnormalities, hemolysis, hemoconcentration, leukogram ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
(139 reference statements)
4
26
1
4
Order By: Relevance
“…However in these tiger snake cases the effect was delayed several days rather than hours. In vitro studies of other venoms have also shown that increasing doses of venom increase the degree of red cell membrane changes and spherocyte formation, particularly with viper venoms (Goddard et al, 2011;Walton et al, 1997). However, in this series, as with an earlier human study (Churchman et al, 2010), there was no clear correlation seen between the observed circulating venom levels and the severity of clinical effects such as the presence or absence of haemolysis.…”
Section: Discussioncontrasting
confidence: 55%
“…However in these tiger snake cases the effect was delayed several days rather than hours. In vitro studies of other venoms have also shown that increasing doses of venom increase the degree of red cell membrane changes and spherocyte formation, particularly with viper venoms (Goddard et al, 2011;Walton et al, 1997). However, in this series, as with an earlier human study (Churchman et al, 2010), there was no clear correlation seen between the observed circulating venom levels and the severity of clinical effects such as the presence or absence of haemolysis.…”
Section: Discussioncontrasting
confidence: 55%
“…Hematological effects consistent with significant derangement of coagulation included marked thrombocytopenia, depletion of serum fibrinogen, prolonged prothrombin, and activated partial thromboplastin time [24]. The group C prothrombin activators in brown snake venom closely resemble mammalian prothrombinase (Xa:Va) which converts prothrombin into thrombin; thus the venom activates coagulation resulting in a consumptive coagulopathy termed venominduced consumptive coagulopathy [26]. …”
Section: Venom Pathogenesis and Poisoning In Australiamentioning
confidence: 99%
“…The most commonly observed clinical manifestations of renal abnormalities after snake envenomation in humans and dogs are acute kidney injury (AKI), proteinuria and hematuria (Sitprija, 2006;Kanjanabuch and Sitprija, 2008;Goddard et al, 2011) The majority of studies and reports of snake envenomation in dogs have focused on routine serum analyses and only to some extent on urinalysis (Heller et al, 2007;Lervik et al, 2010;Gilliam and Brunker, 2011;Sutton et al, 2011). Nevertheless, these parameters are nonspecific and insensitive as they are only altered at the point when about 50 -75% of renal function is already lost (Finco, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As a highly vascularised organ and also as a major elimination route of the snake venom, human and animal kidneys are very susceptible to nephrotoxic effects of envenomation (Sitprija, 2006;Kanjanabuch and Sitprija, 2008;Mello et al, 2010). Kidney injury after envenomation in humans, dogs and rats was reported to be caused either by a direct action of venom or an indirect action through inflammatory mediators, and nephrotoxic effects of myo-and haemoglobin, hypovolemia, disseminated intravascular coagulopathy (DIC) and renal ischemia (Sitprija, 2006;Mello et al, 2010;Goddard et al, 2011;Jacoby-Alner et al, 2011). Renal pathology inflicted by snake venom involves all renal structures, i.e.…”
Section: Introductionmentioning
confidence: 99%